(untitled) (Research, Society and Development, 2021)
Dental caries is an ecological disease of multifactorial origin that has prevailed for centuries and continues to generate great worldwide concern despite all monitoring and control. The introduction of cariogenic foods in childhood, coupled with deficient oral hygiene habits, contribute to the development of caries, implying quality of life. This study aims to evaluate the relationship between cariogenic foods in school meals and the experience of caries in children attended at a public school in Recife. This is a cross-sectional and analytical research with a population composed of 179 children using markers of the ceo-d and DMFT and food consumption index. Results showed an average carbohydrate intake of 173.01g, of which 135.34g (78.23%) for food provided by the school and 37.67g (21.77%) for food brought from home. The mean values of ceo-d and CPO-D for the age group were 1.91 and 0.30 for children with age between 4 to 7 years, 2.0 and 0.44 for children with age between 7 to 9 years, 0.40 and 1.20 for children with age between 10 to 11 years. It was observed that the ceo-d and CPO-D indices present divergent values according to the age group, confirming the presence of risk factors such as frequency of consumption of carbohydrate-rich foods, poor oral hygiene and presence of microbiota cariogenic. A balanced diet, coupled with adequate habits of oral hygiene and periodic visits to the dentist, is necessary for the prevention of early decay.